2017
DOI: 10.1017/s0007114517002008
|View full text |Cite
|
Sign up to set email alerts
|

Processed red meat contribution to dietary patterns and the associated cardio-metabolic outcomes

Abstract: Evidence suggests that processed red meat consumption is a risk factor for CVD and type 2 diabetes (T2D). This analysis investigates the association between dietary patterns, their processed red meat contributions, and association with blood biomarkers of CVD and T2D, in 786 Irish adults (18-90 years) using cross-sectional data from a 2011 national food consumption survey. All meat-containing foods consumed were assigned to four food groups (n 502) on the basis of whether they contained red or white meat and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 25 publications
3
23
1
2
Order By: Relevance
“…The third dietary pattern did not show any associations with PUFA. The negative association of the fourth dietary pattern, with DHA and total n -3 PUFA is similar to that reported previously [ 43 ], and is likely owing to a diet high in meat and meat products being associated with higher n -6 PUFA than n -3 PUFA [ 44 ].…”
Section: Discussionsupporting
confidence: 85%
“…The third dietary pattern did not show any associations with PUFA. The negative association of the fourth dietary pattern, with DHA and total n -3 PUFA is similar to that reported previously [ 43 ], and is likely owing to a diet high in meat and meat products being associated with higher n -6 PUFA than n -3 PUFA [ 44 ].…”
Section: Discussionsupporting
confidence: 85%
“…Red meat is also an important source of protein, Fe, vitamin D and vitamin B 12 (21) . Nevertheless, high intakes have been associated with increased risk of heart disease (35) and diabetes (36) in observational studies, although no such association was observed in the current cohort (28) . To mitigate any such risk the World Cancer Research Fund recommends a weekly intake of three portions (≤500 g) of red meat (37) , with Irish guidelines suggesting 50-75 g of cooked lean red meat daily (38) .…”
Section: Discussioncontrasting
confidence: 71%
“…Omega-3 was associated with, individual components of the MD as well as with the overall mMDS. Diet quality scores such as the Alternate Healthy Eating Index [52,53], Brazilian Healthy Eating Index [54] and the Diet Quality Index [55] have also been positively associated with omega-3 levels. This raises the question of whether omega-3 could potentially be validated as a biomarker for diet quality.…”
Section: Discussionmentioning
confidence: 99%